2016
DOI: 10.1159/000445440
|View full text |Cite
|
Sign up to set email alerts
|

Serum Procalcitonin as a Biomarker for the Prediction of Bacterial Exacerbation and Mortality in Severe COPD Exacerbations Requiring Mechanical Ventilation

Abstract: Background: Procalcitonin (PCT) is being used as a marker of bacterial infections. Although there are several studies showing the diagnostic yield of PCT to differentiate bacterial involvement in chronic obstructive pulmonary disease exacerbations (COPDE), the prognostic yield of PCT in severe COPDE has been studied less. Objectives: The primary aim was to determine whether the level of serum PCT at admission in severe COPDE serves as a prognostic biomarker for hospital mortality. The secondary aim was to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…In a meta-analysis, Ni W et al showed that the sensitivity and speci city of PCT in diagnosing bacterial infections were 0.60 and 0.76, and AUC of ROC curve was 0.77 [44]. Ergan B et al found that compared with culture-negative patients, PCT was markedly increased in culture-positive patients in AECOPD [45]. Their data also showed that 0.25 ng/ml was the optimal cut-off value, with 63% sensitivity, 67% speci city, and 0.73 AUC, to predict bacterial infection in AECOPD.…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis, Ni W et al showed that the sensitivity and speci city of PCT in diagnosing bacterial infections were 0.60 and 0.76, and AUC of ROC curve was 0.77 [44]. Ergan B et al found that compared with culture-negative patients, PCT was markedly increased in culture-positive patients in AECOPD [45]. Their data also showed that 0.25 ng/ml was the optimal cut-off value, with 63% sensitivity, 67% speci city, and 0.73 AUC, to predict bacterial infection in AECOPD.…”
Section: Discussionmentioning
confidence: 99%
“…PCT is a precursor of the hormone calcitonin, and PCT is expressed in neuroendocrine cells of the intestine and the lung (39). PCT has been proposed to have a prognostic importance in exacerbations of COPD (40,41). SAA is a member of the apolipoprotein family, which contributes to the aggravation of the inflammatory response through activation of neutrophil and other inflammatory cells (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…We thank Giorgi-Pierfranceschi et al [1] for their interest in our study [2] . Antibiotic decision in severe chronic obstructive pulmonary disease (COPD) exacerbations is always a dilemma, especially in critically ill patients with acute respiratory failure.…”
mentioning
confidence: 95%